ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PUSAT INFORMASI KONSELING MAHASISWA (PIK-M) PADA MAHASISWI PRODI D III KEBIDANAN STIKES MARANATHA KUPANG - Yosefa Sarlince Atok (STIKes CHMK, 2020)
Background : The Indonesia Government Program in addressing and preventing problems of teenagers is the provision of reproductive health services place which readily accepted and affordable among them through counselling and information center for students (PIK-M). Purpose : The purpose of this research is to know the relationship of knowledge, attitude, motivation, information, facility, socialisation and promotion, and SDM of PIK-M against utilization PIK-M. Method : This research is using cross sectional design. Sampling technique that used in this research is total sampling with 101 people as the sample. Data collected by questionnaire then analyzed using univariable, bivariable, and multivariable. Results : The result of this research shows that from 101 respondents, the 35,6% of the respondents already come visit and use PIK-M. 73,3% of the respondents already have high knowledge about PIK-M, 72,3% of the respondents show positive behavior towards PIK-M, 64,4% of the respondents already have high motivation about PIK-M, 32,7% of the repondents said they already got informations about PIK-M, 72,3% of the respondents already have high facility, 63,4% of the respondents already have high socialisation an promotion, and 83,2% of the respondents already have high SDM about PIK-M. This result shows that the utilization of PIK-M that based on the variables has significant differences. Conclusion : This research is that influence the utilization of PIK-M by students of D III Midwifery Stikes Maranatha, based on the level of knowledge, attitude, motivation, source of information, facility, socialization and promotion, and SDM PIK-M. Suggestion: increase the willingness of students to take advantage of PIK-M. Keyword : Facility, Socialization and promotion, SDM, utilization of PIK-M.